Temporal changes of seismicity in Salton Sea Geothermal Field due to distant earthquakes and geothermal productions - Li, Chenyu (2023)
The Salton Sea Geothermal Field (SSGF) is one of the most seismically active and geothermally productive fields in California. Here we present a detailed analysis of short-term seismicity change in SSGF from 2008 to 2013 during and right following large distant earthquakes, as well as long-term seismicity change due to geothermal productions. We first apply a GPU-based waveform matched-filter technique (WMFT) to the continuous data recorded by the Calenergy Borehole (EN) Network and detect more than 70 000 new micro-earthquakes than listed in the standard Southern California Seismic Network catalogue. We then analyse the seismicity rate changes in the SSGF associated with transient stress fluctuations triggered by regional and large teleseismic earthquakes from 1999 to 2019. We find triggered seismicity in the SSGF following seven regional M > 5.5 earthquakes. In comparison, most teleseismic earthquakes with M > 8.0 did not trigger significant seismicity rate change in the SSGF, likely indicating a frequency dependence in remote dynamic triggering. We further characterize the correlation between the long-term seismicity rate and geothermal production rates, and the temporal and spatial distribution of Guttenberg-Richter b-values inside and outside the SSGF with the newly detected catalogue. The long-term seismicity shows that events with M > 1.5 are likely correlated with net production rates, while smaller events do not show any correlation. The b-values inside the SSGF are higher than those outside the SSGF, and the locations of dynamically triggered events are close to locations with high b-values.